Technology based method to boom the Vocabulary Acquisition of health practitioner students in EFL learning: Effectiveness and Perception - Rizkiyah, Faiqotur; Wulandari, Fitriya Dessi (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2023)
Adapting to the technology development, telegram as one of the accessible social media is used to integrate EFL learning of non English students to the vocabulary acquisition. The health practitioner students have serious difficulties in mastering vocabularies related their subject. Teaching and learning to the subject then integrated technology-based method by implementing telegram quiz bot to boom their vocabulary acquisitions. 30 students of health science were interviewed and asked to fill questionnaire about their perception towards the method and its effectiveness. Data, taken from interview, questionnaire and observation then analyzed by data display, reduction and drawing conclusion. Restating the result, students stated that learning vocabulary by doing quiz in telegram successfully increase their interest in learning EFL. They claimed to be easier in memorizing some vocabularies since the quiz bots provides interactive and colorful features. They did outline that their vocabulary acquisition increased in significant number after experiencing the method.